Gill, Kidney and Liver Structure of Pangasius polyuranodon from The Pinang Luar Oxbow Lake, Buluhcina Village Siak Hulu Sub District Riau Province - Febriyola, Jenika; Windarti, Windarti; Efizon, Deni (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
AbstractPangasius polyuranodon is present in the Pinang Luar lake. Residue of palm plantation activities such as fertilizer, pesticide as well as soil particles may enter the water and negatively affect the health of fish in general. A study aims to understand the histological structure of the gill, kidney and liver of the fish   has been conducted in December-February 2021. Fish organs were histologically processed and stained with HE. Abnormality and damage of the gill was noted and categorized using Histological Alteration Index. Results shown that the types of abnormality present were hyperplasia, hypertrophy and necrosis. In the gills of 2 fishes, there were Dactylogirus sp and Myxobolus sp parasites that may caused the gill damage. The HAI value of the fish ranged from 1 to 102 (category I – III),  indicates that the gill of P. polyuranodon from the Pinang Luar lake is categorized as normal to  high damage. The histological structure of kidney and liver are normal. In general, histological structure of the gill, kidney and liver of the fish from the Pinang Luar lake are healthy.Keywords:Secondary Lamella, Hyperplasia, Histopathological Alteration Index, Dactylogirus sp.